Promoting Physical Activity and Science Learning in an Outdoor Education Program. - Finn, Kevin E.; Yan, Zi; McInnis, Kyle J. (JOPERD: The Journal of Physical Education, Recreation & Dance, 2018)
Outdoor education programs have been shown to have a positive effect on the educational, physical and emotional development of youth. They are increasingly being used to foster a sense of community in schools and to provide students with learning opportunities related to the environment. This article describes an integrated outdoor education program aimed at increasing physical activity and science knowledge among elementary school children in an economically disadvantaged urban community. Results from a study that was conducted showed that activity levels were significantly higher and sedentary time was significantly lower during the outdoor education program compared to the rest of the school day. Schools can utilize outdoor education programs to promote physical activity and improve science learning in elementary school children.